Digital press in the public library - Guallar, Javier; Abadal, Ernest (Anuario ThinkEPI, 2008)
We describe the activities and concerns of public library professionals with respect to the digital press, beginning with comments made by librarians themselves in the forums of different editions of a virtual course organized by the Germ.n S.nchez Ruip.rez Foundation, "La hemeroteca digital" (the digital press). After general comments about the importance of improving users´ utilization of digital press resources, various public library initiatives related to the acquisition, digitalization and dissemination of digital press are described. First, with respect to digital press acquisition, we emphasize the growing trend toward paid subscriptions. Secondly, recent digitalization experiments of interest are discussed. Finally, some dissemination examples of clipping services and web resource guides developed by public libraries are presented.
Keywords: Digital press; Public libraries; Acquisitions; Digitalization; Clipping services.